Coordination skills to excell ski jumping technical skills - Popova, A. I.; Ardashev, A. E.; Prokopenko, G. Y.; Klimov, E. D. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to offer a new coordination skills test model for the modern ski jumping sport.Methods and structure of the study. We made a theoretical analysis for the study knowing the modern ski jumping trampoline systems and based on our practical coaching service to the national ski jumping elite. We sampled for the co-ordination skills tests the 10-21-year-old male ski jumpers (n=124) qualified Junior Class athletes to Masters of Sport. The sample was tested by the following tests: static equilibrium rating test on an unstable T-shape balance plate fixed parallel or perpendicular to the wall to obtain the individual Sagittal Balance and Frontal Balance test data; and the following overall coordination skills rating tests with the spatial orientation test elements: figure-of-eight shuttle sprint test; and the specific low-limb coordination skills rating 10 hurdles jump test. The resulting test data were analyzed versus the ski jumping tech-nique scores.Results and conclusion. The coordination skills excellence practices were found highly beneficial for progress in the modern ski jumping sport trainings and competitions at every stage of an individual sports career. Competitive accom-plishments in the modern ski jumping sport heavily depend on a harmonious progress in coordination skills, with a special priority in the coordination skills trainings given to the ski jumping practices on a few trampolines with different dimensions and profiles. Such trainings are known to develop high stress tolerance and solution-finding skills in practical ski jumping competitive settings.